Change in planted agricultural land use In Qushtapa area during (2004 - 2017) - ليلى محمد قهرمان (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The Qushtapa area was selected as study area for the purpose of identifying the most important changes in the use of plant agricultural land and non- agricultural land (forest + pasture) during the study period (2004 – 2017). The study area has a range of natural and human factor that affect both directly and indirectly on the use of agricultural land and non- agricultural land and positive and negative changes which occur in the cultivated area and the production of agricultural crops during this period. The results showed an a positive change in land area by more than half (55.91)%, production is much larger (530.39)%.The percentage of change varied by type of production.